Impact of central haemodynamics on left ventricular function in individuals with an exaggerated blood pressure response to exercise. Issue 3 (March 2015) - Shim, Chi Young; Hong, Geu-Ru; Park, Sungha; Yang, Woo-In; Choi, Donghoon; Chung, Namsik; Ha, Jong-Won
Abstract : Objective: The impact of exaggerated blood pressure response (EBPR) to exercise on left ventricular function and the mechanism of its association are poorly understood. This study investigated the impact of arterial stiffening on left ventricular function in individuals with an EBPR to exercise. We hypothesized that individuals with low pulse pressure (PP) amplification during exercise would have worse left ventricular function than those with high PP amplification in individuals with an EBPR to exercise. Methods: Fifty-nine individuals with an EBPR to exercise (18 men, age 57 ± 12 years) and 59 age and sex-matched controls were studied. Radial artery tonometry was performed at rest and immediately after exercise during supine bicycle exercise echocardiography. Results: There were no differences in left ventricular structure or function between individuals with an EBPR to exercise and controls. When individuals with an EBPR to exercise were divided into two groups on the basis of PP amplification after exercise [Group 1 ( n  = 30), high PP amplification after exercise; Group 2 ( n  = 29), low PP amplification after exercise], group 2 showed larger left atrial volume and lower early diastolic ( e ') and systolic ( S ') mitral annular velocities. Left ventricular apical rotation was also exaggerated in group 2. In multiple regression, PP amplification after exercise was an independent determinant of e' ( β  = 0.16, P  = 0.019) and S' ( β  = 0.25, P  = 0.009) in individuals with an EBPR to exercise. Conclusion: In individuals with an EBPR to exercise, the degree of left ventricular dysfunction is variable. EBPR to exercise in the presence of arterial stiffening contributes to the deterioration of left ventricular function.